2012
DOI: 10.1002/gps.3768
|View full text |Cite
|
Sign up to set email alerts
|

Determining an appropriate cutting score for indication of impairment on the Montreal Cognitive Assessment

Abstract: Use of the previously suggested cut score of <26 may overpathologize neurologically intact individuals. Further research utilizing ROC curve analysis should be conducted to establish appropriate cutoff scores for various populations which may differ from the present sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
71
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(81 citation statements)
references
References 18 publications
9
71
1
Order By: Relevance
“…Nevertheless, our results already suggest that all MoCA versions show a comparable discriminate power for MCI and AD, which is in line with previous studies [12,36,37]. However, the appropriate cutoff value seems to be population-specific [38], and therefore the discriminative validity and other psychometric measures, such as test-retest reliability, as well as the utility of populationbased norms, should be further addressed in future studies using the MoCA alternate forms, particularly when studying other populations. Due to its indisputable clinical usefulness, the sensitivity of the MoCA and its alternate forms to detect changes across time should be one of the next steps in the further validation of this cognitive measure.…”
Section: Discussionsupporting
confidence: 75%
“…Nevertheless, our results already suggest that all MoCA versions show a comparable discriminate power for MCI and AD, which is in line with previous studies [12,36,37]. However, the appropriate cutoff value seems to be population-specific [38], and therefore the discriminative validity and other psychometric measures, such as test-retest reliability, as well as the utility of populationbased norms, should be further addressed in future studies using the MoCA alternate forms, particularly when studying other populations. Due to its indisputable clinical usefulness, the sensitivity of the MoCA and its alternate forms to detect changes across time should be one of the next steps in the further validation of this cognitive measure.…”
Section: Discussionsupporting
confidence: 75%
“…However, we used a well-tested survey adaptation of a screening tool, the MoCA-SA, 28,39 as well as appropriate cutoffs for a community sample. [42][43][44] A sensitivity analysis utilizing both a continuous cognitive measure and multiple different cutoffs yielded similar associations with social variables (data available on request). Second, the study was cross-sectional, reducing our ability to make causal claims, particularly about whether social or cognitive changes occurred first.…”
Section: Discussionmentioning
confidence: 99%
“…Questions remain regarding most appropriate cutoffs from the MoCA to screen for MCI or dementia; studies from selected clinical samples favor higher cutoff values to define MCI, 38,40,41 compared to community-based studies, [42][43][44] which accept lower cutoffs. We divided the scale into three categories based on community samples: >22 points (normal), 18-22 points (screen positive for MCI), < 18 points (screen positive for dementia).…”
Section: Methodsmentioning
confidence: 99%
“…a more conservative cut-off of <24, and 2.) MoCA scores as a continuous variable, as it has been suggested that the original cut-off may yield low levels of specificity for cognitive impairment (19,20).…”
Section: Cognitive Functionmentioning
confidence: 99%